2008
DOI: 10.5993/ajhb.32.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Behaviors of Chinese Hepatitis B Screening and Vaccination

Abstract: Objective:To measure the knowledge, attitudes, and behaviors of Hepatitis B (HBV) screening and vaccination in the Chinese American population. Methods: A crosssectional study was conducted among 429 Chinese in New York City. Participants were recruited from Chinese community-based organizations. Descriptive statistics and chi-square tests of independence were conducted. Results: Knowledge level of HBV risk factors and screening and vaccination rates are low. There were significant differences in screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 6 publications
6
46
3
Order By: Relevance
“…53 Knowledge of specific and general medical information has been linked to health behaviors such as screening. 50,51,[54][55][56][57] Findings from the present study suggest that Chinese Americans with higher collectivism views were more willing to participate in biospecimen research compared with those with less collectivism views, although this did not remain significant in multivariate analyses. Collectivists value actions with benefits to society and social life [23][24][25][26][27][28] and so support medical research by being willing to donate blood.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…53 Knowledge of specific and general medical information has been linked to health behaviors such as screening. 50,51,[54][55][56][57] Findings from the present study suggest that Chinese Americans with higher collectivism views were more willing to participate in biospecimen research compared with those with less collectivism views, although this did not remain significant in multivariate analyses. Collectivists value actions with benefits to society and social life [23][24][25][26][27][28] and so support medical research by being willing to donate blood.…”
Section: Discussioncontrasting
confidence: 63%
“…Indeed, Chinese American participants in other focus groups and key informant studies conducted by our Center expressed their desire to participate in health screenings and biospecimen banking to help their community and the next generation. 7,8,54,55,57 The measure of Yin-Yang used in this study reflects both the importance of maintaining a balance but also beliefs about western medicine and traditional health practices. 13,[31][32][33] In bivariate analyses, those with higher Yin-Yang beliefs were more unwilling to participate in biospecimen research (mean scores of 43.5 vs. 40.4, p = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Given the substantial proportion of migrants in China's urban population, HBV discrimination is an important health and social issue in China. Previous studies 4,6,13 found that knowledge about HBV was low in rural Chinese populations, Asian immigrants 18,19 and Chinese immigrants. 12,18,20 In our study, HBV-related knowledge consisted of knowledge about HBV symptoms, consequences if untreated, treatment regimes and transmission routes.…”
Section: Discussionmentioning
confidence: 96%
“…Patients' understanding of transmission and disease treatment has been found to deviate from clinical knowledge and recommendations. 22,[41][42][43][44] Continuing medical education (CME) for providers in HBV transmission might serve to bridge the gaps.…”
Section: Discussionmentioning
confidence: 99%